Simulation study and experimental validation on the effect of generator blade type and arrangement on maximum torque generated for micro hydropower generator - Mohd Haniff Hazmin,; Faizal Mustapha, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This paper contributes to an ongoing development of a micro hydropower network system tailored for implementation along river networks in Malaysia. The concept involves deploying multiple micro hydropower generators to charge a battery positioned on the riverbank. This interconnected hydropower network work alongside similar network systems to either charge larger batteries or serve multiple communities, enhancing its scalability and utility. The primary aim of this study is to determine a better generator blade type, and explore the relationship between the arrangement of generator blades in the river and the resulting torque generated. An experiment is conducted to determine the superior turbine type. The simulation process integrates engineering simulation software (ANSYS) and 3D modeling software (CATIA). ANSYS is employed to simulate river conditions with specific flow rates, while CATIA facilitates the design of generator blades, subsequently imported into ANSYS for simulation. The objective of the simulation is to identify the blade arrangement yielding the highest maximum generated torque. Subsequently, an experiment involving 3D printing the selected turbine types and measuring their rotational speed under consistent water flow conditions using a digital tachometer is conducted. From the experiment, it is found that curved blade types outperform straight blade types, while from the ANSYS simulation it is found that a distance between generator blades ranging from 300mm to 400mm offers optimal performance. This comprehensive approach enables a thorough evaluation of turbine configurations and their real-world performance, advancing micro hydropower technology for sustainable energy generation along river networks.